The Legal Position of Digital Forensic Experts in the Settlement of Information Technology Crime Cases - Indriati Amarini; Rizky Aulia Cahyadri; Maulida Ayu Fitriani; Noorfajri Ismail (Lex Scientia Law Review, 2024)
Digital forensic expert testimony is required by judges to resolve cases related to information technology. However, there are allegations of violations committed by certain parties on several servers such as illegal access, configuration changes, and shutdowns. This is increased by the destruction of crime scene and digital evidence.  In some cases, analyzing the data collected can be time-consuming, and practical understanding is needed by judges to avoid irrelevant questions for digital forensic experts in court. Therefore, this research aims to determine and analyze forensic digital experts in court hearings, the duties and roles of judges in resolving information and technology cases as well as the position of forensic experts in the judicial process. The doctrinal research is sourced from secondary data in the form of Electronic Information and Transaction laws, criminal procedure laws, research reports, books, and scientific journals. The results show that digital forensics expert testimony is needed to assist judges as gatekeepers in obtaining material truth. Practical digital forensic knowledge is used to increase the efficiency of case examination time by avoiding irrelevant questions. Best practices are used in the actions, procedures, handling, and analysis of electronic evidence as well as digital forensic expert testimony in judicial practice.